The Impact of Using Task-Based Activities on Iranian EFL Learners’ Speaking Skill - Atefeh Shamsy; Rasoul Mombeini (EDUVELOP, 2021)
This study explored the impacts of task-based activities on Iranian intermediate EFL learners’ speaking skill. To do the current study, the Oxford Quick Placement Test (OQPT) was given to 75 students and 50 intermediate participants whose scores were between 40 and 47 were selected. Then, the participants were randomly divided into two groups; one experimental group and one control group. Then they were given three topics to talk about in two minutes as a speaking pre-test. Afterwards, the experimental group received the treatment through task-based activities while the control group received a traditional instruction. The whole instruction lasted eight sessions. In the first two sessions, the OQPT and the pre-test were administered, respectively; in five sessions, the participants received the treatment, and in the eighth session, the post-test of speaking was given to the participants of both groups to measure the effects of the treatment on their speaking improvement. The collected data were analyzed through independent and paired samples t-tests and the results indicated that the experimental group outperformed the control group on the post-test. In other words, there was a significant difference between the speaking post-test of the two groups. The implications, the conclusions, the limitations, and the suggestions of the research were explained.